Telling the story the heart and soul of successful leadership - Mead, Geoffrey (Chichester Jossey-Bass, 2014)
"Telling the Story is both practical (with tips, exercises and examples) and thought provoking. It argues for a re-enchantment of our disenchanted world and for the recognition of more human and humane values in our organizational lives.The art of narrative leadership is important for senior executives, middle managers and concerned citizens.Distilling the author?s considerable experience as a public service leader, research academic, organizational consultant, performing storyteller and leadership coach on top management programmes, Telling the Story shows how leaders affect our understanding of what is possible and desirable through the stories they tell and the stories they live. It opens a door into the world of narrative leadership: what stories are and how they work; when to tell a story and how to tell one well; how the stories we tell (and the language and metaphors we use) influence our actions and shape the way we think about the world. The book also challenges us to consider the purposes behind our stories: what are we leading for? What are the big stories of our time and how can our own stories help to create the kind of future we want for ourselves and our children?
Includes bibliographical references and index.
Keywords: Leadership